2016
DOI: 10.1037/hea0000262
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver responses to early cleft palate care: A mixed method approach.

Abstract: Objective This study sought to understand caregivers’ (CGs’) responses to early cleft lip/palate care for their infants. Method A prospective, mixed methods multicenter longitudinal study was conducted among CGs (N=118) seeking treatment for their infants’ cleft lip and palate or cleft lip only at one of six cleft treatment centers in the United States. Participants were in one of two treatment groups: traditional care only or nasoalveolar molding (NAM) plus traditional care. The CGs completed semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 46 publications
2
78
1
1
Order By: Relevance
“…An alternative explanation could be that surgery may have a point of diminishing returns. While the timing of surgery and number of procedures may be important to individuals’ OHRQoL, these results suggest that adjunct psychological counseling could provide support to patients and their families undergoing the stress and expectations associated with surgery [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation could be that surgery may have a point of diminishing returns. While the timing of surgery and number of procedures may be important to individuals’ OHRQoL, these results suggest that adjunct psychological counseling could provide support to patients and their families undergoing the stress and expectations associated with surgery [36, 37]. …”
Section: Discussionmentioning
confidence: 99%
“…Responders reported the extent to which 17 DSM‐IV PTSD symptoms had bothered them in the past month, with responses ranging from not at all (1) to extremely (5). Neurodegenerative conditions often cause neuropsychiatric symptoms in the form of anxiety and elevated depressive symptoms [26]; however, recent work has shown that re‐experiencing symptoms are less sensitive to increases in symptomatology seen in cognitively impaired individuals, so the focus in this study was on the symptoms [27]. PTSD symptom severity denotes symptoms summed across the five re‐experiencing symptoms in a standard way and scaled to range from no symptoms (0) to maximal symptoms (1) to facilitate effect size comparison.…”
Section: Methodsmentioning
confidence: 99%
“…After 1178 exclusions, five studies were read in full text. As a result of full text screening, four articles [21], [22], [23], [24] were excluded with reasons (Table 4) and one study [16] met the inclusion criteria and were included in the qualitative analysis.…”
Section: Summary Measures and Synthesis Of Resultsmentioning
confidence: 99%
“…Because of the handicapping nature of the infants, the success of PSIO depends mainly on the parents' positive interaction and commitment. Several studies [16], [21], [22], [23], [24], [25], [26], [27] evaluated the parents' satisfaction while dealing with the PSIO. They measured the amount of load on the parents, while carrying out the procedures of taking care of their child in this period.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation